Quantitative portrait of open access mega-journals - Erfanmanesh, Mohammadamin (Malaysian Journal of Library and Information Science, 2019)
Nowadays, Open Access Mega-Journals (OAMJs) represent a substantial part of the scholarly communication system. The current research is conducted with the aim of providing better insights into the increasingly important OAMJ phenomenon through investigation of eight reputable titles using established bibliometric methods. Results of the study showed that eight studied OAMJs were responsible for 1.87% of the total number of publication indexed in Web of Science during 2012-2016. Despite the decline in publication count of PLOS ONE over the past couple of years, it was the biggest journal in the world till 2017, when Scientific Reports overtook PLOS ONE as the most productive journal. Over 88% of the papers published in eight selected OAMJs were cited at-least once at the point in time of analysis. The highest proportions of cited and un-cited documents were seen in Scientific Reports and SpringerPlus, respectively. With regard to the three indicators, namely share of highly-cited papers, the category normalized citation impact as well as the JIF percentile, IEEE Access had by far the best performance among eight examined OAMJs. Results of the study revealed that Biochemistry & Molecular Biology, Multidisciplinary Sciences, Neurosciences, Oncology and Immunology were the most commonly assigned subject categories to OAMJs’ content. The National Natural Science Foundation of China was the most important funding agency that supported the publication of around 26000 articles in eight studied OAMJs. Investigation of the geographic distribution of authors showed that the United States and China by far had the highest contribution in the content of eight studied OAMJs. There were, however, notable variations between different OAMJs.